The projection from dorsal medial prefrontal cortex to basolateral amygdala promotes behaviors of negative emotion in rats - Cai, Youqing; Ge, Jianlong; Pan, Zhizhong Z. (Frontiers in Neuroscience, 2024)
Brain circuits between medial prefrontal cortex (mPFC) and amygdala have been implicated in cortical control of emotion, especially anxiety. Studies in recent years focus on differential roles of subregions of mPFC and amygdala, and reciprocal pathways between mPFC and amygdala in regulation of emotional behaviors. It has been shown that, while the projection from ventral mPFC to basomedial amygdala has an anxiolytic effect, the reciprocal projections between dorsal mPFC (dmPFC) and basolateral amygdala (BLA) are generally involved in an anxiogenic effect in various conditions with increased anxiety. However, the function of the projection from dmPFC to BLA in regulation of general emotional behaviors under normal conditions remains unclear. In this study, we used optogenetic analysis to identify how this dmPFC-BLA pathway regulates various emotional behaviors in normal rats. We found that optogenetic stimulation of the dmPFC-BLA pathway promoted a behavioral state of negative emotion, increasing anxietyand depressive-like behaviors and producing aversive behavior of place avoidance. Conversely, optogenetic inhibition of this pathway produced opposite effects, reducing anxiety-and depressive-like behaviors, and inducing behaviors of place preference of reward. These findings suggest that activity of the dmPFC-BLA pathway is sufficient to drive a negative emotion state and the mPFC-amygdala circuit is tonically active in cortical regulation of emotional behaviors.